2017
DOI: 10.3389/fmicb.2017.02051
|View full text |Cite
|
Sign up to set email alerts
|

A Linear 19-Mer Plant Defensin-Derived Peptide Acts Synergistically with Caspofungin against Candida albicans Biofilms

Abstract: Public health problems are associated with device-associated biofilm infections, with Candida albicans being the major fungal pathogen. We previously identified potent antibiofilm combination treatment in which the antifungal plant defensin HsAFP1 is co-administered with caspofungin, the preferred antimycotic to treat such infections. In this study, we identified the smallest linear HsAFP1-derived peptide that acts synergistically with caspofungin or anidulafungin against C. albicans as HsLin06_18, a 19-mer pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 45 publications
1
24
0
Order By: Relevance
“…It was also suggested that this defensin may also be involved in the inhibition of yeast-to-hypha transition, but the mechanism of this process remained undefined. Similar observations were described in another report, indicating a synergistic action of a smaller linear HsAFP1-derived peptide (HsLin06_18) with several echinocandins (caspofungin, micafungin and anidulafungin) against C. albicans [ 107 ]. These substances also significantly reduced in vitro biofilm formation on catheters by C. glabrata and caspofungin-resistant C. albicans strains.…”
Section: A New Perspective For Plants’ Components In Antifungal Thsupporting
confidence: 86%
“…It was also suggested that this defensin may also be involved in the inhibition of yeast-to-hypha transition, but the mechanism of this process remained undefined. Similar observations were described in another report, indicating a synergistic action of a smaller linear HsAFP1-derived peptide (HsLin06_18) with several echinocandins (caspofungin, micafungin and anidulafungin) against C. albicans [ 107 ]. These substances also significantly reduced in vitro biofilm formation on catheters by C. glabrata and caspofungin-resistant C. albicans strains.…”
Section: A New Perspective For Plants’ Components In Antifungal Thsupporting
confidence: 86%
“…In addition to the SMIC, the BIC-2 (BIC 50 ), is the minimum compound concentration resulting in a 2-fold inhibition of biofilm formation. Similarly, the BEC-2 (BEC 50 ) is the minimum compound concentration resulting in a 2-fold eradication of mature biofilms 92 93 . In practice, to assess biofilm inhibition, compounds are included during the biofilm growth phase.…”
Section: Methods For Antifungal Susceptibility Testing Of Biofilmsmentioning
confidence: 99%
“…The diversity of synthetic peptides entering clinical trials has increased over the last 13 years, stimulating advances in Fmoc SPPS technologies in response to the growing demand for medicinal chemistry and pharmacology (Behrendt et al, 2016). Several groups have synthesized linear (Tran et al, 2008;Magliani et al, 2011;Konno et al, 2015;Cools et al, 2017;Park et al, 2018) and cyclic peptides (Mosca et al, 2000;Schaaper et al, 2001;Konno et al, 2015;Ng-Choi et al, 2019) using Fmoc SPPS.…”
Section: Chemical Synthesismentioning
confidence: 99%